Stem cambial variants of Taiwan lianas - Sheng-Zehn Yang; Po-Hao Chen; Jian-Jhong Chen (Botanical Studies, 2022)
Abstract Background Cambium in lianas, responsible for secondary growth, develop diverse and diagnostic traits during the climbing phase. Studies on the cross-section of Taiwanese liana cambial variants are scarce. We collected multiple stem cross-sections from 287 liana species belonging to 52 families. Each sample was examined on five occasions, and the observations were documented. Results The results showed that approximately 22 cambial variants types were displayed in Taiwan lianas. Among these, axial vascular elements in radial segments were the most common, followed by the variants with the irregular conformation and intraxylary phloem. Based on our assessment, we provide the following identification features of a few families: Apocynaceae had intraxylary phloem; Convolvulaceae had intraxylary phloem combined with successive cambia; Lardizabalaceae, Menispermaceae, and Ranunculaceae possessed axial vascular elements in segments; Piperaceae had external primary vascular bundle cylinder combined with axial vascular elements in segments; Vitaceae had axial vascular elements in segments combined with irregular conformation. Axial vascular elements in segments and intraxylary phloem appeared in six or five combination types, showing that these two types combined with many variants are helpful for the identification of lianas. Two species, Momordica charantia var. abbreviata, and Momordica cochinchinensis had a cambium element in the outer cylinder of cortical bicollateral vascular bundles and formed directional layers of successive cambia. Conclusions Our study documented regular secondary growth with a single cambium in 36 species and cambial variants present in 16 species of Taiwanese lianas. Furthermore, we provide crucial baseline data on liana cambial variations, thereby improving our understanding of their morphology and identification.